СПЕЦИФІКА ФУНКЦІОНУВАННЯ СТРУКТУР УКРАЇНСЬКОЇ ГРЕКО-КАТОЛИЦЬКОЇ ТА РУСЬКОЇ ПРАВОСЛАВНОЇ ЦЕРКОВ У СХІДНІЙ ГАЛИЧИНІ В УМОВАХ РАДЯНСЬКОЇ МОДЕЛІ ДЕРЖАВНО-ЦЕРКОВНИХ ВІДНОСИН (1945–1965 РР.) - Лагодич, Микола (My University, 2022)
Lahodych M.M. The specific features of the Ukrainian Greek Catholic and Russian Orthodox church structures functioning in the Eastern Galicia under the condition of the Soviet model of church-state relations (1945–1965s.) – Manuscript (219 р.). Thesis for a Candidate Degree in History. Speciality 09.00.11 – Religious studies. – National University of Ostroh Academy. – Ostrog, 2014. The thesis dwells upon the peculiarities of the Soviet state policy regarding the existing structures of the Ukrainian Greek Catholic and Russian Orthodox churches in the Eastern Galicia.The research is based upon archival sources and the available historiography of the subject.The given paper analyzes the forms and methods of state policy regarding these churches, their reaction to the policy and its consequences. Thus the characteristic features in the development of these religious institutions in the given area can be traced: the structure, activities, problems, transformations, etc. Within the framework of this research we have also analyzed the process of establishing a control system over religious organizations in the form of two special state bodies. The latter being the Council for Russian Orthodox Church and the Council in matters of worship with the corresponding state bodies at the level of the Soviet Union republics and separate regions. The role of the Soviet authorities in the creation of the «Initiative Group for the reunification of the Greek Catholic Church with the Orthodox Church» and in conducting the Lviv Synod in 1946 has also been studied in this paper. This research also characterizes the process of formation and the activity of the Orthodox eparchies in the Eastern Galicia and studies the condition of the UGCC in the Soviet underground and the phenomenon of the so-called “pokutnytstvo”. The given paper reveals the peculiarities of the economic policy and the atheist propaganda, as the means of influencing the religious life of the region. The given research justifies the periodization of the religious buildings’ closing and elimination process, emphasizes the region-based policy peculiarities of the party-state structures regarding the church structures. This thesis also identifies the reasons of the forced decrease of the religious network. It has been concluded that the elimination of the religious buildings in the East Galicia, most active in the late 1950s and early 1960s, was a purposeful vector of the state policy, carried out in accordance with the ideological priorities of the Soviet Union Communist Party, the USSR and Ukrainian SSR authorities and determined by the peculiarities of the public – political transformations in the country. Within this research we have also dwelled upon the process of creating Orthodox periodicals in the East Galicia and opening the Orthodox seminary in Lviv Key words: state policy, Eastern Galicia, church-state relations, Ukrainian Greek Catholic Church, Russian Orthodox Church, Moscow patriarchy, Vatican, Lviv church synod, commissary Council in the matters of ROC, “pokutnytstvo”, seminary, «Eparchy herald».
2014
Keywords: державна політика, Східна Галичина, державно-церковні відносини, Українська греко-католицька церква, Руська православна церква, Московський патріархат, Ватикан, Львівський церковний собор, уповноважений, Рада у справах релігій, Рада у справах РПЦ, покутництво, семінарія, Єпархіальний вісник; state policy, Eastern Galicia, church-state relations, Ukrainian Greek Catholic Church, Russian Orthodox Church, Moscow patriarchy, Vatican, Lviv church synod, commissary Council in the matters of ROC, “pokutnytstvo”, seminary, «Eparchy herald»